The Impact of Private Capital Flows on South Africa's Developmental State Agenda in the Post-Apartheid Era - Mokoena, Itumeleng (Department of Political Studies, 2021)
This dissertation explores the impact of private capital flows on South Africa's developmental state agenda in the post-apartheid era. South Africa is one country that has set, beforehand, the objective to become a developmental state. However, the role of private capital flows as a factor that can determine the success, or the failure of that objective is largely missing from the debate about constructing the developmental state in South Africa. By exploring the impact of private capital flows, the study seeks to inform the reader about the nature and composition of private capital flows in South Africa as well as investigate whether these flows hinder or accelerate South Africa's developmental state objective. The study has utilized qualitative methods. It also made use of quantitative data as a secondary supplement to ensure a greater understanding of the research problem. In addition, the study has used the theory of financialization from Marxist Political Economy which posits that private capital flows are unproductive and merely interested in surplus accumulation without producing anything substantive in the long term. The research findings indicate that financial liberalization as a step that was taken by the democratic government to attract private capital flows has not been beneficial for South Africa's long term development as it allows capital flight and illicit financial flows. While South Africa did manage to attract private capital flows after liberalizing its capital account, these flows have been made up mainly of portfolio investments that do not contribute significantly to the productive sectors. Instead, portfolio investments drive excessive household debt, consumption and financial speculation. Moreover, private capital flows reinforce a non-developmental agenda by exacerbating the problem of unemployment, inequality, and poverty which are key developmental goals that South Africa seek to overcome through the developmental state. More importantly, South Africa's reliance on private capital flows constrain its economic policy choices and this, in turn, hinders an emergence of a developmental state.